Martha Stewart's cakes : our first-ever book of bundts, loaves, layers, coffee cakes and more (Clarkson Potter/Publishers, 2013)
A one-stop resource for cakes--birthday, chocolate, coffee, Bundt, upside-down, loaf, and more featuring 150 cakes plus ideas for decorating, gifting, and storing.